Harmonizaton of Judicial Pardon in The 2023 Criminal Code and Criminal Procedure Code: Normative Criticism of the Design of Indonesia’s Modern Penal System - Putri Amaris, Putu Kanitha; Sari Haryanto, Diah Ratna (Westscience Press, 2025)
This study aims to examine the regulatory vacuum of the mechanism for the implementation of judicial pardon which has been materially recognized in Article 54 paragraph (2) of the Criminal Code (KUHP) in 2023. Judicial pardon is a form of modern punishment innovation purpose that represents a paradigm shift from a retributive approach towards substantive justice, by providing space for judges not to impose punishment on perpetrators who are proven guilty in certain circumstances. This research uses normative juridical method with statutory approach and contemporary criminal law concept. There are two main problem formulations analyzed, namely: (1) what is the position and scope of judicial pardon in the national punishment system; and (2) whether the current Indonesian criminal law system has provided an adequate normative basis for its legitimate and accountable implementation. The results showed that normatively, judicial pardon reflects the spirit of renewal of Indonesian criminal law towards a more humanistic system. However, the lack of formal mechanisms in KUHAP and technical implementation guidelines from judicial institutions has caused this norm to be in a non-self-executing position. Thus, regulative harmonization and institutional policies are needed so that the applicability of judicial pardon is not symbolic, but operational in judicial practice.